2015
DOI: 10.1007/s00113-015-0121-9
|View full text |Cite
|
Sign up to set email alerts
|

Geriatrische Frakturzentren

Abstract: The world's population is aging resulting in changes in the way we manage geriatric care. Furthermore, this population has a considerable risk of fragility fractures, most notably hip fractures. Hip fractures are associated with significant morbidity and mortality and have large economic consequences. It is due to these factors that the concept of an elderly trauma center was developed. These trauma centers utilize the expertise in orthopedic and geriatric disciplines to provide coordinated care to the elderly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 21 publications
(11 reference statements)
0
2
1
Order By: Relevance
“…A similar trend could be seen in pulmonary complications and delirium. Thus, our results contradict previous studies, which predominantly observed a reduced detection of the aforementioned complications [9,11]. Fisher et al, for example, were able to demonstrate a reduction in delirium from 11.7 % to 5.9% and a reduction in urinary tract infections from 8.9% to 6.7% in the co-care of older patients with hip fractures [9].…”
Section: Primary Outcome Measurescontrasting
confidence: 99%
See 2 more Smart Citations
“…A similar trend could be seen in pulmonary complications and delirium. Thus, our results contradict previous studies, which predominantly observed a reduced detection of the aforementioned complications [9,11]. Fisher et al, for example, were able to demonstrate a reduction in delirium from 11.7 % to 5.9% and a reduction in urinary tract infections from 8.9% to 6.7% in the co-care of older patients with hip fractures [9].…”
Section: Primary Outcome Measurescontrasting
confidence: 99%
“…While there have been conflicting results on the outcome of ortho-geriatric co-management in the early years [7], numerous studies recently demonstrated a reduction in complications, readmission rates, and mortality [8][9][10]. In addition, as the economic burden of patient care is getting more important, the advantages of such models were analyzed and highlighted by several working groups [11,12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation